The Ability to Selectively Allocateattentional Demands on Walking During Secondary Cognitive and Motor Tasks in Elderly People With and Without a History of Falls - Abbas Bayatloo; Mahyar Salavati; Behnam Akhbari (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: The main goal of this studywas to determine the ability of elderly adults Abstract to selectively allocate attentional demands on walking during secondary motor and cognitive tasks. Methods & Materials: in this prospective three factors mixed design, 33 elderly adultswithout a history of falls and 23 elderly adults with a history of falls were asked to performtimed up and go test (TUG), either alone or simultaneously with secondary cognitive (backward days of week) or motor (transferring coins) tasks under two instructional sets (a) focus primarily on the primary postural task (b) bayatloopt@gmail.com e secondary motor or cognitive tasks. Time and number of steps on TUG, cognitive and motor tasks score were videotaped. demographics, Rehabilitation Sciencsmirnov, independent t-test, two nd three way mixed ANOVA fare and were used for analyzing dciences Tehran, Results: using three way ANOVA to complts with Iran. and without a history of falls to measure the flexibility of allocation of attention, reshowed both groups had ability to allocate attention toward primary postural task and non-fallers represented better attention of allocation than fallers. when participants perform secondary motor task, time of TUG increased compared to cognitive task. Conclusion: our study confirmed thw ability to allocate attention toward the primary task but non-fallers have more attention than fallers. it is suggested that inability to allocate attention could be one important factor among others that contribute to balance constraints during gait in fallers. elderly adults sacrifice performance on the secondary task in order to optimize their gait and balance. 1- Department of physical therapy, University of social Welfare and Rehabilitation Sciences Tehran, Iran.